Features tuberculous etiology meningitis in young children - O. V. Kolokolova; L. V. Kuzmina; O. V. Filinyuk; O. O. Kaminsky; O. A. Novoselova (Бюллетень сибирской медицины, 2012)
The appointment of anti-TB drugs with meningitis tuberculous etiology later than the 10th day of illness in most cases leads to an unfavorable outcome of the disease and the development of serious complications. Specific therapy, conducted by the anti-TB drugs, with a high degree of penetration into the cerebrospinal fluid (isoniazid, pyrazinamide, amikacin, ethionamide) makes it possible to avoid fatal outcome in tuberculous meningitis in children, even at very late diagnosis. For suspected meningitis, and that it cannot be excluded, it is necessary to appoint a trial therapy 3—4 anti-TB drugs while there is a specification of the diagnosis.